Molecular determinants of peri‐apical targeting of inositol 1, 4, 5‐trisphosphate receptor type 3 in cholangiocytes. Issue 10 (19th July 2022) - Rodrigues, Michele A.; Gomes, Dawidson A.; Fiorotto, Romina; Guerra, Mateus T.; Weerachayaphorn, Jittima; Bo, Tao; Sessa, William C.; Strazzabosco, Mario; Nathanson, Michael H.
Abstract: Fluid and bicarbonate secretion is a principal function of cholangiocytes, and impaired secretion results in cholestasis. Cholangiocyte secretion depends on peri‐apical expression of the type 3 inositol trisphosphate receptor (ITPR3), and loss of this intracellular Ca 2+ release channel is a final common event in most cholangiopathies. Here we investigated the mechanism by which ITPR3 localizes to the apical region to regulate secretion. Isolated bile duct units, primary mouse cholangiocytes, and polarized Madin‐Darby canine kidney (MDCK) cells were examined using a combination of biochemical and fluorescence microscopy techniques to investigate the mechanism of ITPR3 targeting to the apical region. Apical localization of ITPR3 depended on the presence of intact lipid rafts as well as interactions with both caveolin 1 (CAV1) and myosin heavy chain 9 (MYH9). Chemical disruption of lipid rafts or knockdown of CAV1 or MYH9 redistributed ITPR3 away from the apical region. MYH9 interacted with the five c‐terminal amino acids of the ITPR3 peptide. Disruption of lipid rafts impaired Ca 2+ signaling, and absence of CAV1 impaired both Ca 2+ signaling and fluid secretion. Conclusion : A cooperative mechanism involving MYH9, CAV1, and apical lipid rafts localize ITPR3 to the apical region to regulate Ca 2+ signaling and secretion in cholangiocytes. Abstract : Proposed model for the roles of MYH9 and CAV1 in localizing ITPR3 to the apical region. Our findings suggest that both MYH9 and CAV1 are necessary for proper localization of ITPR3 to the periapical region. One possible explanation that is consistent with the known roles of these two proteins is that MYH9 is responsible for transporting newly synthesized ITPR3 along actin filaments to the apical region, while CAV1 is responsible for maintaining apical ITPR3 in proximity to lipid rafts in the apical membrane. Maintenance of this apical pool of ITPR3 then permits the local Ca 2+ signals that are necessary for secretion.image